Effect of NaOH Concentration on Magnetic Properties and Structural Studies of MgFe2O4 Based on Natural Iron Sand Synthesized by Co-Precipitation Method - Shiamny Nur Khair Tarigan; Syahrul Humaidi; Martha Rianna; Nurul Maulida R Nasution (IKIP Mataram, 2023)
This research was conducted to synthesize MgFe2O4 using the coprecipitation method by varying the concentration of NaOH. In this study, MgCl26H2O, iron sand, 37% HCl and variations of NaOH (5 M and 10 M) were mixed at 90 ℃ for 60 minutes, then washed using distilled water and ethanol until pH = 7, and calcined at 750 ℃. The test results using X-Ray Diffraction (XRD) showed that the diffraction pattern of phase formation identified was MgFe2O4 with hkl values (220), (311), (400), (422), (511), and (440). The resulting crystal size decreased with the addition of NaOH concentration. The test results using a Vibrating Sample Magnetometer (VSM) show that the magnetization value decreases when the crystal size decreases.